Simona Scotti, Emanuela Claudia del Re (coord.), Spirito&Spirits. Religioni e Lifestyles, Roma, Aracne, 2019 - Gervasi, Francesco (Comparative Cultural Studies: European and Latin American Perspectives, 2019)
AAVV